The Effect of Recurrent Deficiencies in PCAOB Inspections on Audit Quality within the Big Four Audit Firms in South Africa - Badu, Joseph; Dubihlela, Jobo (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The research aims to examine PCAOB inspection deficiencies' impact on audit quality in South Africa's Big Four, highlighting challenges in maintaining high standards across Financial Statements (FS), Internal Control Over Financial Reporting audits (ICFR), Auditor Ethics, Professional Conduct, and Due Professional Care. The study analyzes South African Big Four firms' audit work and its impact on audit quality, focusing on four PCAOB inspection deficiencies: FS and (ICFR) audits, Auditor Ethics/Independence, Professional Conduct, and Due Professional Care and Scepticism. The study used a mixed-method (qualitative and quantitative) case study approach. A self-administered questionnaire was used to collect primary data. Secondary data was collected from existing literature and inspection reports. The test results indicate that the identified deficiencies significantly influence audit quality, establishing a strong connection between these deficiencies and the audit quality of Big Four firms. The findings suggest that recurrent deficiencies in PCAOB inspections have a negative effect on audit quality within the Big Four Audit Firms in South Africa, concluding that deficiencies in these variables (Integrated Audits of FS and ICFR, Auditor Ethics and Independence, Professional Misconduct, and Due Professional Care and Professional Scepticism) can adversely affect the overall audit quality of the Big Four firms.